2020
DOI: 10.2307/j.ctv13xpsvw
|View full text |Cite
|
Sign up to set email alerts
|

Fabricate 2020

Abstract: As the editors of FABRICATE 2020, we have many people to thank. We received over 250 submissions from 45 countries; we would like to thank everyone who responded to the call for works, for the extraordinary breadth, depth and quality of the work submitted that made the exacting process of review, selection and curatorship so challenging. We are grateful to all authors and collaborators on every selected project, and everyone who generously agreed to present their work.We are indebted to more than 50 distinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
0
12
0
2
Order By: Relevance
“…The same constraints of traditional AM are present in mycelium printing, although the need to preserve cell viability through the control of feedstock type, morphology, distribution, and porosity adds an extra layer of difficulty (84,85). Burry et al (71) showed that inter-and intralayer adhesion in mycelium prints can be improved by a cell-secreted extracellular polymeric substance that bonds and physically interlocks with the lignocellulosic substrate, as mentioned in the previous sections.…”
Section: Fungal Inksmentioning
confidence: 99%
“…The same constraints of traditional AM are present in mycelium printing, although the need to preserve cell viability through the control of feedstock type, morphology, distribution, and porosity adds an extra layer of difficulty (84,85). Burry et al (71) showed that inter-and intralayer adhesion in mycelium prints can be improved by a cell-secreted extracellular polymeric substance that bonds and physically interlocks with the lignocellulosic substrate, as mentioned in the previous sections.…”
Section: Fungal Inksmentioning
confidence: 99%
“…Особенности составов для 3D-печати связаны с отсутствием, как правило, крупного заполнителя (более 5 мм). Максимальный размер зерен для строительных «чернил» не превышает 2-3 мм [114,115]. В связи с этим для полного смачивания таких дисперсных систем требуется больше воды, что в свою очередь может приводить к повышению усадки при высыхании.…”
Section: табл 1 примеры некоторых составов для 3d-печатиunclassified
“…The design was an organic process, where The design team thoroughly investigated each line of thought and interrogated the result, this was not a linear journey and involved exploring many avenues of thought in tandem. [60]…”
Section: ➢ Generationmentioning
confidence: 99%
“…Once the 3D model was created, data could be extracted or grouped to enable a simple selection of individual plates or portions of the Vessel. [60]…”
Section: ➢ Evaluationmentioning
confidence: 99%